Fetal alcohol spectrum disorder resources for educators: A scoping review. (26th January 2022) - Lees, Briana; Riches, Julia; Mewton, Louise; Elliott, Elizabeth J.; Allsop, Steve; Newton, Nicola; Thomas, Sue; Rice, Lauren J.; Nepal, Smriti; Teesson, Maree; Stapinski, Lexine A.
Abstract: Children with foetal alcohol spectrum disorder (FASD) can experience neurodevelopmental, physical, psychological and behavioural impairments that can result in a disrupted school experience. However, educators often have limited knowledge or experience in the identification and support of students with FASD, and there is a critical need for effective tools and resources to ensure students with FASD are supported in their ongoing learning and development. This scoping review aimed to identify and evaluate publicly available educator resources that aid in the identification, and support of students with FASD in primary/elementary school. In addition, educators and FASD experts were consulted to obtain feedback on currently available resources, and key issues and priorities for FASD resources. In total, 124 resources were identified by searching peer‐reviewed and grey literature databases, app stores, podcast services and contacting FASD experts. Information was found on identification (23 resources) and support of students with FASD (119 resources). No resources provided information on the referral. Most resources were average (40%) to good (33%) quality, as measured by a composite tool based on adaptions of the NHMRC FORM Framework and iCAHE Guideline Quality Checklist. A minority of resources had been formally evaluated (7%). Review findings and consultations with experts and educators indicate a critical need for referral guides, evidence‐based short‐format resources and centralised access for school communities to high‐quality resources. Taken together, this study has identified key areas for future resource development and research to better support primary school students with FASD.